Analysis of Sustainable Competitive Advantage Influenced by Organizational Culture and Leadership Behavior through Technological Innovation - Putra Pratama; Besar Agung Martono (Journal GoodWill, 2024)
This study analyzes the influence of organizational culture and leadership behavior on sustainable competitive advantage through technological innovation as an intervening variable in the two-wheeler spare parts and metal stamping manufacturing industry, particularly at PT. NKP in Bogor Regency. Using a quantitative approach, data were collected from 84 middle and top-level leaders through questionnaires and direct observation. The data were analyzed using the Smart Partial Least Squares (PLS) version 3.0 method to test measurement and structural models. The results reveal that leadership behavior and organizational culture significantly affect both technological innovation and sustainable competitive advantage. Furthermore, technological innovation acts as a significant mediating variable strengthening the indirect relationship between organizational culture, leadership behavior, and competitive advantage. The findings demonstrate that visionary and participative leadership fosters an innovative organizational climate that encourages creativity and continuous improvement. Similarly, an adaptive and collaborative organizational culture provides a conducive environment for innovation, thereby enhancing the firm’s ability to sustain competitiveness in a dynamic market. This research confirms that technological innovation is not only a strategic tool but also a key determinant linking human and cultural factors to sustainable organizational success. The study offers theoretical implications for strategic management and practical insights for manufacturing firms aiming to enhance their innovation capabilities and maintain long-term competitiveness.